The Role of Episodic Context in Retrieval Practice Effects - Whiffen, Joshua W; Karpicke, Jeffrey D (Journal of experimental psychology. Learning, memory, and cognition, 2017)
The episodic context account of retrieval-based learning proposes that retrieval enhances subsequent retention because people must think back to and reinstate a prior learning context. Three experiments directly tested this central assumption of the context account. Subjects studied word lists and then either restudied the words under intentional learning conditions or made list discrimination judgments by indicating which list each word had occurred in originally. Subjects in both conditions experienced all items for the same amount of time, but subjects in the list discrimination condition were required to retrieve details about the original episodic context in which the words had occurred. Making initial list discrimination judgments consistently enhanced subsequent free recall relative to restudying the words. Analyses of recall organization and retrieval strategies on the final test showed that retrieval practice enhanced temporal organization during final recall. Semantic encoding tasks also enhanced retention relative to restudying but did so by promoting semantic organization and semantically based retrieval strategies during final recall. The results support the episodic context account of retrieval-based learning.